AW-NI-3: EFFECTS OF RENAL DENERVATION ON LEFT AND RIGHT VENTRICULAR FUNCTION IN HYPERTENSIVE RATS WITH HEART FAILURE INDUCED BY VOLUME OVERLOAD. (January 2023) - Miklovic, Matus; Gawrys, Olga; Kala, Peter; Honetschlagerova, Zuzana; Jichova, Sarka; Vanourkova, Zdenka; Huskova, Zuzana; Kikerlova, Sona; Mracek, Tomas; Sedmera, David; Maxova, Hana; Melenovsky, Vojtech
Abstract : Objective: Clinical studies showed that renal denervation (RDN) is effective in blood pressure lowering in hypertension. Previously, we found that RDN prolongs survival in a hypertensive rodent model of heart failure due to volume overload from aorto-caval fistula (ACF). Whether it is due to afterload removal, or due to intrinsic effects of RDN on the right (RV) or left (LV) ventricular function, is currently unknown and was the focus of our investigation. Design and method: 8-week-old Ren-2 transgenic male rats (model of angiotensin II-dependent hypertension) underwent ACF surgery to induce volume overload. After one week, animals underwent bilateral RDN (mechanical and chemical by topical phenol application) from laparotomy. Two weeks after RDN, the functions of both ventricles were measured by simultaneous biventricular pressure-volume analysis, and the animals were examined using echocardiography each week. Results: RDN in ACF rats only slightly reduced maximum pressure in RV but did not affect maximum pressure in LV. Yet, RDN in ACF animals significantly reduced hypertrophy and dilatation of both ventricles and decreased lung and liver congestion. RDN in ACF rats improved load-independent measures of contractility of both ventricles (end-systolic elastance and preload recruitable stroke work). RDN in ACF rats reduced renal levels of norepinephrine (NE) but restored depleted NE both in RV and LV. At the gene expression level, RDN in ACF led to favorable remodeling which was reflected as increased transcription of beta-1 adrenergic receptors in LV and beta-2 adrenergic receptors in RV and LV, decreased transcription of natriuretic peptide A gene (NPPA), collagen 1, and monoaminoxidase A (MAOA). These changes were relatively more pronounced in RV than LV. Interestingly, RDN in ACF rats also significantly inhibited the activity of neprilysin in the kidney. Conclusions: Besides the effects on pressure, RDN favorably affected load-independent measures of chamber function, markers of myocardial remodeling, and restored myocardial norepinephrine levels. These data indicate that RDN effects extend beyond pressure lowering and could be a promising method in the treatment of both right and left ventricular heart failure.